Genomic Characterization of Carbapenem-Non-susceptible Pseudomonas aeruginosa Clinical Isolates From Saudi Arabia Revealed a Global Dissemination of GES-5-Producing ST235 and VIM-2-Producing ST233 Sub-Lineages - Doumith, Michel; Alhassinah, Sarah; Alswaji, Abdulrahman; Alzayer, Maha; Alrashidi, Essa; Okdah, Liliane; Aljohani, Sameera; , NGHA AMR Surveillance Group; Balkhy, Hanan H.; Alghoribi, Majed F.; Alghoribi, Majed F.; Okdah, Liliane; et al. (Frontiers in Microbiology, 2022)
Carbapenem-resistant P. aeruginosa has become a major clinical problem due to limited treatment options. However, studies assessing the trends in the molecular epidemiology and mechanisms of antibiotic resistance in this pathogen are lacking in Saudi Arabia. Here, we reported the genome characterization in a global context of carbapenem non-susceptible clinical isolates from a nationally representative survey. The antibiotic resistance profiles of the isolates (n=635) collected over 14 months between March 2018 and April 2019 from different geographical regions of Saudi Arabia showed resistance rates to relevant β-lactams, aminoglycosides and quinolones ranging between 6.93 and 27.56%. Overall, 22.52% (143/635) of the isolates exhibited resistance to both imipenem and meropenem that were mainly explained by porin loss and efflux overexpression. However, 18.18% of resistant isolates harbored genes encoding GES (69.23%), VIM (23.07%), NDM (3.85%) or OXA-48-like (3.85%) carbapenemases. Most common GES-positive isolates produced GESs -5, -15 or -1 and all belonged to ST235 whereas the VIM-positive isolates produced mainly VIM-2 and belonged to ST233 or ST257. GES and VIM producers were detected at different sampling periods and in different surveyed regions. Interestingly, a genome-wide comparison revealed that the GES-positive ST235 and VIM-2-positive ST233 genomes sequenced in this study and those available through public databases from various locations worldwide, constituted each a phylogenetically closely related sub-lineage. Profiles of virulence determinants, antimicrobial resistance genes and associated mobile elements confirmed relatedness within each of these two different sub-lineages. Sequence analysis located the blaGES gene in nearly all studied genomes (95.4%) in the same integrative conjugative element that also harbored the acc(6’)-Ib, aph(3’)-XV, aadA6, sul1, tet(G) and catB resistance genes while blaVIM-2 in most (98.89%) ST233-positive genomes was co-located with aac(6')-I1, dfrB-5 and aac(3’)-Id in the same class I integron. The study findings revealed the global spread of GES-5 ST235 and VIM-2 ST233 sub-lineages and highlighted the importance of routine detection of rare β-lactamases